The Consulate / Johan @ Eddy Luaran … [et al.] - Luaran, Johan@Eddy; Mohd Rom, Kamarol Baharen; Ahmad Nadzri, Fazyudi; Mohd Shahrom, Syahreena (Research Innovation Business Unit, 2014)
The Consulate is a product which was invented after we discovered that most of the students have difficulties in identifying materials that conduct electricity. This subtopic comes under the theme of investigating material in Science Curriculum Primary 4. This product consists of 2 model house which consist of many types of materials. By using the house as a model, the students will be able to learn better because these are the materials they encounter every day. The consulate was developed systematically using ADDIE model and has been tested in one of the primary school in Shah Alam. The feedback shows that the students were able to grasp the concept of electricity with the help of this house model. Positive responses were also received from the science teacher.